Analisis Wacana Berita Kontroversi Gus Miftah dan Penjual Es Teh di Kompas.com dan Detik.com Edisi 1-4 Desember 2024 - Rahmadi, Kelik Tri (IAIN Madura, 2025)
The derogatory remark goblok made by Miftah Maulana Habiburrahman, also known as Gus Miftah, directed at Sunhaji, an iced tea seller, during a religious gathering in Magelang on November 20, 2024, sparked controversy from various parties. This study aims to answer the following questions: How was the controversy between Gus Miftah and the iced tea seller constructed in news reports by Kompas.com and Detik.com during the December 1–4 editions How does Norman Fairclough’s discourse analysis apply to the news coverage of this controversy in Kompas.com and Detik.com editions from December 1–4, 2024. This research is a literature study using a qualitative approach. The study employs Norman Fairclough’s discourse analysis method, which includes the dimensions of text, discursive practice, and social practice. The focus of this research is on the textual dimension, which covers aspects of representation, relations, and identity. The results of the study are as follows: The construction of the two news articles from Kompas.com and Detik.com regarding the controversy falls into the category of soft news and overall fulfills the 5W1H elements of news reporting. Based on Norman Fairclough’s discourse analysis, in terms of representation, both Kompas.com and Detik.com show a mix of support and criticism regarding the controversy. In terms of relations, both platforms feature participants who express both pro and contra stances. In terms of identity, Kompas.com tends to maintain a neutral stance, while Detik.com leans toward a critical position against Gus Miftah’s remarks.